Responsibilization and MNC-stakeholder engagement: Who engages whom in the pharmaceutical industry? - Frederick Ahen (Springer, 2022)
Within the context of the pharmaceutical industry, there are numerous controversial issues that have still not received satisfactory answers. In this era of neo-liberal capitalism, ‘responsibilizing’ every stakeholder announces the freedom of the MNCs from regulations and productive stakeholder engagement for enacting sincere corporate social responsibility (CSR) practices. More prominently, as the current level of global health inequalities demonstrates, the twenty-first century stakeholders of the firm are for the most part on their own, although this remains an implicit design in CSR discourses. This reasoning stems from the fact that unlike the proximate and influential stakeholders, these distal and fragile stakeholders remain faceless, invisible and nameless, given their lower socio-economic and political status. Pharmaceutical MNC–stakeholder controversies are not new, but the legitimating tactics of the firm obscure the material needs of stakeholders—especially those of the marginalized and distal stakeholders in emerging economies. The managerial and strategic recipes for stakeholder engagement are manifold, and yet a lot remains to be understood about who engages whom in responsibly creating the maximum social value (health benefits). This is the research question this study seeks to answer. Employing an inductive approach, I use ‘Big Pharma’ as a case that bases arguments on extant literature as ‘authorities of prima facie evidence’ to outline the industry-specific questions whilst questioning the existing answers.
Stakeholder Engagement: Clinical Research Cases